Data mining–based analysis to explore the application of an animal model of diabetic gastroparesis - Xu, Hui; Miao, Fu-rui; He, Yu-jun; Fan, Yu-shan (Frontiers in Endocrinology, 2025)
ObjectiveThis review aims to study the characteristics of animal models of diabetic gastroparesis, provide a reference for the standardization of model preparation, and offer a better experimental basis for researching its pathogenesis and diagnosis-treatment strategies.MethodsBy searching databases including PubMed, Web of Science, China Knowledge Network, Wanfang Data Knowledge Service Platform, and China Science and Technology Journal Database, we obtained literature on diabetic gastroparesis animal experiments from 2000 to 2024. We assessed the literature for the risk of bias using the Systematic Review Center for Laboratory Animal Experimentation tool. We summarized the animal species, sex, modeling methods, modeling criteria, detection indexes, etc.; established a database using Excel software; and applied SPSS Modeler 18.0 and Cytoscape 3.7.2 to analyze the characteristics of diabetic gastroparesis animal models.ResultsA total of 211 articles were included. It was found that Sprague–Dawley rats were the primary animal model, with male rats predominantly used in modeling. Modeling methods primarily included a one-time injection of streptozotocin (60–65 mg/kg) to induce type 1 diabetic gastroparesis or a one-time injection of streptozotocin (40–55 mg/kg) combined with a high-sugar and high-fat irregular diet to induce type 2 diabetic gastroparesis. Most studies set the modeling period as 8 weeks after drug administration. Blood glucose, general condition, and gastric emptying rate were commonly used as modeling criteria, and domperidone served as the positive control drug. Main detection indexes included blood glucose, general condition, gastrointestinal function dynamics, histopathological analysis, immunohistochemistry, Western blotting, etc.ConclusionThere is no recognized modeling method and evaluation standard for diabetic gastroparesis animal models. On the basis of the results of data analysis, it is recommended to use a one-time injection of streptozotocin (60–65 mg/kg) to induce type 1 diabetic gastroparesis animal model or a one-time injection of streptozotocin (40–55 mg/kg) combined with irregular feeding of high-sugar and high-fat feed to induce type 2 diabetic gastroparesis animal model. Blood glucose, general condition, and gastric emptying rate were used to judge the models.